Challenges of maintaining highly specialised infrastructure facilities at an institution of higher learning in South Africa - Hlophe, Matholi (Department of Construction Economics and Management, 2025)
Facilities management (FM) plays a crucial role in the success of higher education institutions. This study explores the challenges that facilities managers encounter in performing routine maintenance work and the impact of inadequate maintenance on highly specialised facilities at a South African higher education institution. The primary aim of this study was to understand the challenges associated with maintaining highly specialised infrastructure such as biosafety containment laboratories, pre-clinical laboratories, and research clean rooms. The objectives include investigating the reason senior academics are reluctant about routine maintenance, challenges experienced by the facility managers when conducting maintenance, assessing the impact of these challenges on academic activities, identifying key factors that contribute to maintenance difficulties, and to make recommendations towards improving infrastructure management. The study employed an interpretivist paradigm with an accompanying qualitative research approach. A single case study of a higher education institution in South Africa was utilised. Data was collected via semi-structured interviews with facilities managers, maintenance personnel, contractors as well as senior academics managing or using these highly specialised facilities at the selected higher education institution. A total of 22 interviews were undertaken and the data analysed using thematic analysis. The study found that the primary reasons for senior academics' resistance to routine maintenance include disruptions to ongoing academic activities, lack of communication and stakeholder engagement, and concerns about expertise and safety, and their limited knowledge on the facility maintenance requirements. Facilities managers face significant challenges due to administrative bottlenecks, insufficient support from higher management, and ineffective project governance, including lack of formalised contractual agreements and regulatory frameworks. Budget constraints, communication barriers, fragmented communication systems, a lack of a centralised communication mechanism further exacerbate these issues as these impede the efficient dissemination of maintenance information to the relevant stakeholder(s). Furthermore, old infrastructure and a reactive maintenance culture led to frequent breakdowns. In addition, rapid technological advancements result in frequent equipment obsolescence and high maintenance costs resulting to further disruptions. To address these challenges enhanced stakeholder engagement and involvement is needed together with improved communication channels and the establishment of robust governance frameworks to ensure timely and effective maintenance of highly specialised facilities. Recommendations emanating from this study include: adopting proactive maintenance strategies to prevent equipment failures before they occur; enhancing training for technical staff to ensure they are equipped to maintain specialised equipment; improving monitoring systems to better predict maintenance needs; securing sustainable funding models to support ongoing maintenance and equipment upgrades; and lastly, involving the facility managers in the design phase of the infrastructure and in the planning of the academic calendar. These strategies aim to promote timely implementation and completion of maintenance projects, reduce costs, and ensure sustainable maintenance practices in higher education institutions. This research provided valuable insights and a framework for other institutions facing similar challenges, contributing to the broader field of infrastructure management in higher education.